Influence of circadian rhythms on sports performance. (2nd November 2021) - Ayala, Victoria; Martínez-Bebia, Manuel; Latorre, Jose Antonio; Gimenez-Blasi, Nuria; Jimenez-Casquet, Maria Jose; Conde-Pipo, Javier; Bach-Faig, Anna; Mariscal-Arcas, Miguel
ABSTRACT: Chronobiology is the scientific discipline of study of biological rhythms, a term that has gained ground in the sports world. Recently numerous studies have indicated that the time of day in which sports are practiced influences the achievement of good physical performance. The aim of this review was to study the relationship between circadian rhythms and physical performance, according to the latest published data. In addition, the physiological processes involved in the physical response and the differences according to the type of sport and athletes' characteristics were studied. A bibliographic search was carried out through five databases (Pubmed, Scopus, Researcher Gate, Google Scholar, UOC Library), focusing on articles published in the last ten years and written in English and Spanish. 36 papers met the inclusion criteria. Body temperature is a factor that shows a circadian pattern with a marked peak in the later afternoon, time of the day at which physical performance is at its highest, i.e. speed, agility, distance covered, jumping power. The perception of effort is also higher in the afternoon. Regarding the chronotype, evening types seem to be the most affected to do sports out of their optimal time-of-day. The tendency shows more morning types as age increases. Training sessions should be planned according to the optimal time of day for each athlete. It's essential to take into account individual chronotype. The desynchronization of circadian rhythms can cause a decrease in physical performance.